Bondable alloy surface slurry for LTCC (low temperature co-fired ceramic) co-firing and preparation method of bondable alloy surface slurry
By developing a bondable metal slurry for LTCC co-fired bondable metal slurry containing micron-grade gold powder and SiO2-B2O3-CaO glass powder, the existing LTCC electronic paste has solved the problems of poor electrical performance in the millimeter wave band and warping during sintering, and achieved excellent electrical performance and bonding tension.
Patent Information
- Application Number
- CN202411944162.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
The existing LTCC electronic paste has poor electrical performance in the millimeter wave frequency band, and warping, layering and curling are prone to problems during sintering, affecting the electrical performance of the conductive gold paste.
A bondable metal slurry for LTCC co-fired, containing 75~85% of the micron-level gold powder functional phase, 0.5~2% of SiO2-B2O3-CaO-based glass powder and 18~20% of the organic carrier. Through process steps such as stirring and multiple rolling, the fineness and viscosity of the slurry are optimized, and the bonding tensile force and electrical properties of the gold slurry are improved.
It realizes LTCC electronic paste with excellent electrical properties in the millimeter wave frequency band, with a bonding tension of ≥7gf@25μm Au wire, reducing warping and layering problems during sintering, and is suitable for commercial high-frequency Ferro A6 raw porcelain.
Smart Images

Figure CN119638490A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of LTCC and relates to a bondable alloy paste for LTCC co-firing and a preparation method thereof. Background Art
[0002] Low Temperature Co-fired Ceramics (LTCC) technology is increasingly developing towards high density, small size, three-dimensional components, and high frequency. The new generation of wireless communication technologies in application fields such as 5G communications, intelligent transportation, intelligent Internet of Things systems, and wearable medical applications have an increasing demand for high operating frequency, wide bandwidth, and low-loss millimeter-wave low-loss materials. LTCC electronic pastes used in millimeter-wave frequency bands are also the core basic materials for the development of millimeter-wave communication systems, millimeter-wave radar systems, millimeter-wave imaging systems, and millimeter-wave electronic countermeasure systems.
[0003] At present, among the conductor metals used in electronic pastes, silver has the highest conductivity, followed by copper, and gold has the second highest conductivity. However, gold is generally much more resistant to chemical corrosion and discoloration than silver and copper, and does not melt, discolor, oxidize, or ablate at a high temperature of 1000°C; therefore, gold paste has higher chemical stability and the ability to work in harsh environments. At present, there is still a problem of co-firing mismatch between domestic pastes and substrates. During the co-firing process of paste and raw tape, the matching between substrate and paste affects each other, but the former is more selective to the latter. For surface solderable gold conductor paste, the printed substrate will have problems such as warping, delamination, and curling during the sintering process, which affects the electrical properties of the conductive gold paste. Therefore, it is necessary to develop a gold surface paste with excellent electrical properties, low warpage, and excellent bonding tension in the millimeter wave frequency band to solve the above problems. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a bondable alloy paste for LTCC co-firing and a preparation method thereof. The developed LTCC electronic paste has excellent electrical properties in the millimeter wave frequency band and excellent bonding tension, meeting ≥7gf@25μm Au wire.
[0005] The technical solution provided by the present invention is as follows:
[0006] The invention provides a bondable alloy paste for LTCC co-firing. The bondable alloy paste comprises, by mass percentage, 75-85% of a micron-sized gold powder functional phase, 0.5-2% of an inorganic bonding phase and 18-20% of an organic carrier; the micron-sized gold powder comprises flaky gold powder and spherical gold powder, and the mass ratio of the flaky gold powder to the spherical gold powder is 5:3.
[0007] Furthermore, in the micron-sized gold powder functional phase, the D50 of the flake gold powder is 4±0.5 μm, and the D50 of the spherical gold powder is 2±0.5 μm.
[0008] Furthermore, the inorganic binder phase is SiO2-B2O3-CaO glass powder, which includes 22.8% by weight of SiO2, 41.2% by weight of B2O3 and 36% by weight of CaO, and the D50 of the SiO2-B2O3-CaO glass powder is 1±0.5 μm.
[0009] Furthermore, the organic carrier includes 65-85% by weight of an organic solvent, 10-30% by weight of a polymer thickener, and 1-5% by weight of a thixotropic agent.
[0010] Furthermore, the organic solvent is selected from any one or more of diethylene glycol monobutyl ether, diethylene glycol butyl ether acetate or alcohol ester dodecahydrate.
[0011] Furthermore, the polymer thickener is ethyl cellulose.
[0012] Furthermore, the thixotropic agent is selected from any one or more of hydrogenated castor oil and polyamide resin.
[0013] The present invention also provides a method for preparing the above-mentioned bondable gold surface paste for LTCC co-firing, comprising the following steps: uniformly stirring the micron-level gold powder functional phase, the inorganic bonding phase and the organic carrier according to the ratio to obtain a fully mixed paste; rolling the paste for multiple times until the fineness and viscosity of the paste meet the requirements of screen printing, and obtaining the bondable gold surface paste after filtering.
[0014] Furthermore, the preparation method of the inorganic binder phase includes: Weigh CaO, B2O3 and SiO2 according to the ratio and put them into a ball mill. Use the ball mill to mix evenly and then dry the mixture. Then pour it into a platinum crucible and melt it at 1300-1500°C for 1-2 hours. Pour the molten glass liquid into deionized water for quenching. Take out the quenched material and perform secondary ball milling. After the secondary ball milling, filter the material with a 1000-mesh sieve and dry it for later use.
[0015] Furthermore, the stirring evenly comprises: In a ball mill, premix with a planetary gravity mixer at a low speed of 600-700 r / min for 30-60 s, then mix at a speed of 1200-1300 r / min for 60-90 s and at a speed of 800-900 r / min for 100-150 s to obtain a fully mixed slurry; The slurry is subjected to multiple rolling processes including: The mixed slurry is rolled on a three-roll mill for 8 to 10 times, wherein the roller spacing of the three-roll mill is adjusted between 5 and 100 μm; The slurry fineness that meets the requirements of screen printing is less than 20μm and the viscosity is 120~280Pa·s.
[0016] Beneficial Effects
[0017] The bondable gold face paste for LTCC co-firing of the present invention can match with Ferro A6 green porcelain used in commercial high frequency; the amount of glass powder added in the gold face paste of the present invention is reduced, while the specific gravity of the organic adhesive is increased; there is no glass powder interval between the gold powders during the rolling process of the gold paste, which is prone to post-sintering polymerization; the rolling parameters are optimized, the dispersion of the paste is enhanced, and an excellent LTCC electronic paste is obtained, the resistivity of which is less than 3.0mΩ / sq@10μm, the bonding tension is ≥7gf@25μm Au wire, and the paste has excellent electrical performance and reliability; the process window is wide, and the paste is compatible with the general LTCC substrate manufacturing process and the group packaging process. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The process diagram of the preparation of the bondable alloy paste for LTCC co-firing of the present invention;
[0019] Figure 2 It is a schematic diagram of rolling the bondable alloy paste for LTCC co-firing of the present invention;
[0020] Figure 3 This is a physical picture of the bondable alloy paste for LTCC co-firing of the present invention;
[0021] Figure 4 It is a schematic diagram of printing the bondable alloy paste for LTCC co-firing of the present invention. DETAILED DESCRIPTION
[0022] The embodiment of the present invention provides a bondable alloy paste for LTCC co-firing. The bondable alloy paste comprises, by mass percentage, 75-85% of a micron-sized gold powder functional phase, 0.5-2% of an inorganic bonding phase and 18-20% of an organic carrier; the micron-sized gold powder comprises flaky gold powder and spherical gold powder, and the mass ratio of the flaky gold powder to the spherical gold powder is 5:3.
[0023] In this embodiment, the D50 of the flake gold powder in the micron-sized gold powder functional phase is 4±0.5 μm, and the D50 of the spherical gold powder is 2±0.5 μm.
[0024] In this embodiment, the inorganic binder phase is SiO2-B2O3-CaO glass powder, which includes 22.8% SiO2, 41.2% B2O3 and 36% CaO by weight, and the D50 of the SiO2-B2O3-CaO glass powder is 1±0.5μm.
[0025] In this embodiment, the organic carrier includes 65-85% by weight of an organic solvent, 10-30% by weight of a polymer thickener, and 1-5% by weight of a thixotropic agent.
[0026] In this embodiment, the organic solvent is selected from any one or more of diethylene glycol monobutyl ether, diethylene glycol butyl ether acetate or alcohol ester dodecahydrate.
[0027] In this embodiment, the polymer thickener is ethyl cellulose.
[0028] In this embodiment, the thixotropic agent is selected from any one or more of hydrogenated castor oil and polyamide resin.
[0029] The present invention also provides a method for preparing the above-mentioned bondable gold surface paste for LTCC co-firing, comprising the following steps: uniformly stirring the micron-level gold powder functional phase, the inorganic bonding phase and the organic carrier according to the ratio to obtain a fully mixed paste; rolling the paste for multiple times until the fineness and viscosity of the paste meet the requirements of screen printing, and obtaining the bondable gold surface paste after filtering.
[0030] Specifically, the preparation method comprises the following steps:
[0031] 1. Organic carrier preparation
[0032] Weigh 5 parts of diethylene glycol monobutyl ether, 5 parts of diethylene glycol butyl ether acetate and 65 parts of alcohol fat 12 in a sealed jar and mix them evenly. Then weigh 15 parts of ethyl cellulose and mix them slowly (try to avoid ethyl cellulose forming large clumps). Place them in a homogeneous reactor, set the temperature to 80°C, set the speed to 80r / min, and dissolve for two hours to obtain a uniform ethyl cellulose solution. Then add 5 parts of hydrogenated castor oil and 5 parts of polyamide resin, and continue mixing for 30 minutes under the same conditions to obtain an organic carrier mixture.
[0033] 2. Glass powder production (inorganic binder phase)
[0034] CaO, B2O3 and SiO2 are weighed according to the weight ratio and loaded into a ball mill for 24 hours at a ball milling speed of 100-200 rpm. After ball milling, the raw materials are taken out and dried, loaded into a platinum crucible and melted at 1300-1500°C for 1-2 hours, and the molten glass liquid is poured into deionized water for quenching. The quenched material is taken out for secondary ball milling. The material after the secondary ball milling needs to be sieved through a 1000-mesh sieve and dried for standby use.
[0035] 3. LTCC bondable alloy paste
[0036] The organic carrier, glass binder phase and functional phase (including flaky gold powder and spherical gold powder) were weighed according to mass percentage and placed in a ball mill. They were premixed for 30-60 seconds at a low speed of 600-700 r / min using a planetary gravity mixer, and then mixed for 60-90 seconds at a speed of 1200-1300 r / min and for 100-150 seconds at a speed of 800-900 r / min to obtain a fully mixed slurry. The mixed slurry was then rolled on a three-roll mill for 8-10 times, with the roller spacing of the three-roll mill adjusted between 5 and 100 μm. After the particles inside the slurry were well dispersed, the fineness test (<20 μm) and the viscosity test (120-280 Pa·s) met the requirements, and then the finished slurry required for the experiment was obtained by filtration.
[0037] In this embodiment, the glass powder composition and ratio are shown in Table 1. Three glass powders with different ratios are selected as inorganic bonding phases to prepare surface bonding gold paste (the preparation method of the organic carrier is as mentioned above, and the functional phase is selected as gold powder with a ratio of 5:3 of sheet and ball powder). Different glass powder ratios lead to great differences in sintering matching between the paste and the green tape.
[0038] Table 1 Inorganic binder phase composition
[0039]
[0040] As shown in Table 1, the slurry with CBS1 as the binder phase has the largest warpage after co-firing, which is close to 2mm, while the slurry with CBS2 as the binder phase has a warpage of less than 0.2mm after co-firing, and the slurry with CBS3 as the binder phase has a warpage of about 0.8mm after co-firing. The particle size of the glass powder is controlled at about 1μm D50.
[0041] In this embodiment, the ratio and resistivity of the functional phase metal powder are shown in Table 2. Flake gold powder and spherical gold powder are selected for combined addition to study the effect of the relative addition amount of the two gold powders on the conductivity of the wire. The mass ratio of gold powder in the surface bonding gold paste is 80%, and the bonding paste is prepared according to the ratio of flake powder: spherical powder of 80%:0, 60%:20%, 50%:30%, 30%:50%, 20%:60%, 0:80% (the preparation method of the organic carrier is as described above, and the glass bonding phase is CBS2), and the square resistance test is performed on the sintered wire. The square resistance test results are shown in Table 2.
[0042] Table 2 Wire square resistance after mixing different proportions of tablets and ball powder
[0043]
[0044] As can be seen from Table 2, the square resistance of the conductor shows a trend of first decreasing and then increasing with the decrease of the flake powder content. When all the gold powder used is spherical powder, the square resistance is 4.14mΩ / sq; when the ratio of flake to spherical powder reaches 5:3, the square resistance reaches the minimum value of 2.89mΩ / sq, at which time the resistivity is the smallest; if all flake powder is used, the square resistance value is 4.36mΩ / sq. Therefore, the gold powder with a flake to spherical powder ratio of 5:3 is selected as the functional phase of the gold paste. In the above, the particle size of the spherical gold powder is controlled at about 2μm D50; the particle size of the flake gold powder is controlled at about 4μm D50.
[0045] Embodiment 1-3:
[0046] The embodiment of the present invention provides a method for preparing a bondable alloy paste for LTCC co-firing, and the proportions of the components are as shown in the following table:
[0047] Table 3 Content of each component of LTCC bondable alloy paste of Examples 1-3 (mass percentage)
[0048]
[0049] The preparation method of embodiment 1:
[0050] 1. Organic carrier preparation
[0051] Weigh 5 parts of diethylene glycol monobutyl ether, 5 parts of diethylene glycol butyl ether acetate and 65 parts of alcohol lipid twelve, place in a sealed jar and mix evenly, then weigh 15 parts of ethyl cellulose and slowly (try to avoid ethyl cellulose forming large clumps) mix with them, place in a homogeneous reactor, set the temperature to 80°C, set the speed to 80r / min, and dissolve for two hours to obtain a uniform ethyl cellulose solution. Then add 5 parts of hydrogenated castor oil and 5 parts of polyamide resin, continue mixing for 30 minutes under the same conditions to obtain an organic carrier mixture.
[0052] 2. Glass powder production (inorganic binder phase)
[0053] According to the CBS1 formula, CaO, B2O3 and SiO2 are weighed and loaded into a ball mill for 24 hours at a ball milling speed of 100-200 rpm. After ball milling, the raw materials are taken out and dried, loaded into a platinum crucible and melted at 1300-1500°C for 1-2 hours, and the molten glass liquid is poured into deionized water for quenching. The quenched material is taken out for secondary ball milling. The material after the secondary ball milling needs to be sieved through a 1000-mesh sieve and dried for standby use.
[0054] 3. LTCC bondable alloy paste
[0055] According to the ratio in Table 3, the organic carrier, glass binder phase and functional phase (including flaky gold powder and spherical gold powder) were weighed and placed in a tank, and premixed for 30 seconds at a low speed of 640r / min using a planetary gravity mixer, and then mixed for 60 seconds at a speed of 1260r / min and 120 seconds at a speed of 860r / min to obtain a fully mixed slurry. The mixed slurry was then rolled 8 to 10 times by a three-roll mill, wherein the roller spacing of the three-roll mill was adjusted between 5 and 100μm. After the particles inside the slurry were well dispersed, the fineness test (<20μm) and viscosity test (120 to 280Pa·s) were performed, and the finished slurry required for the experiment was obtained after filtration.
[0056] The preparation method of embodiment 2:
[0057] 1. Organic carrier preparation
[0058] Weigh 5 parts of diethylene glycol monobutyl ether, 5 parts of diethylene glycol butyl ether acetate and 65 parts of alcohol lipid twelve, place in a sealed jar and mix evenly, then weigh 15 parts of ethyl cellulose and slowly (try to avoid ethyl cellulose forming large clumps) mix with them, place in a homogeneous reactor, set the temperature to 80°C, set the speed to 80r / min, and dissolve for two hours to obtain a uniform ethyl cellulose solution. Then add 5 parts of hydrogenated castor oil and 5 parts of polyamide resin, continue mixing for 30 minutes under the same conditions to obtain an organic carrier mixture.
[0059] 2. Glass powder production (inorganic binder phase)
[0060] According to the CBS2 formula, CaO, B2O3 and SiO2 are weighed and loaded into a ball mill for 24 hours at a ball milling speed of 100-200 rpm. After ball milling, the raw materials are taken out and dried, loaded into a platinum crucible and melted at 1300-1500°C for 1-2 hours, and the molten glass liquid is poured into deionized water for quenching. The quenched material is taken out for secondary ball milling. The material after the secondary ball milling needs to be sieved through a 1000-mesh sieve and dried for standby use.
[0061] 3. LTCC bondable alloy paste
[0062] According to the ratio in Table 3, the organic carrier, glass binder phase and functional phase (including flaky gold powder and spherical gold powder) were weighed and placed in a tank, and premixed for 30 seconds at a low speed of 640r / min using a planetary gravity mixer, and then mixed for 60 seconds at a speed of 1260r / min and 120 seconds at a speed of 860r / min to obtain a fully mixed slurry. The mixed slurry was then rolled 8 to 10 times by a three-roll mill, wherein the roller spacing of the three-roll mill was adjusted between 5 and 100μm. After the particles inside the slurry were well dispersed, the fineness test (<20μm) and viscosity test (120 to 280Pa·s) were performed, and the finished slurry required for the experiment was obtained after filtration.
[0063] The preparation method of embodiment 3:
[0064] 1. Organic carrier preparation
[0065] Weigh 5 parts of diethylene glycol monobutyl ether, 5 parts of diethylene glycol butyl ether acetate and 65 parts of alcohol lipid twelve, place in a sealed jar and mix evenly, then weigh 15 parts of ethyl cellulose and slowly (try to avoid ethyl cellulose forming large clumps) mix with them, place in a homogeneous reactor, set the temperature to 80°C, set the speed to 80r / min, and dissolve for two hours to obtain a uniform ethyl cellulose solution. Then add 5 parts of hydrogenated castor oil and 5 parts of polyamide resin, continue mixing for 30 minutes under the same conditions to obtain an organic carrier mixture.
[0066] 2. Glass powder production (inorganic binder phase)
[0067] According to the CBS3 formula, CaO, B2O3 and SiO2 are weighed and loaded into a ball mill for 24 hours at a ball milling speed of 100-200 rpm. After ball milling, the raw materials are taken out and dried, loaded into a platinum crucible and melted at 1300-1500°C for 1-2 hours, and the molten glass liquid is poured into deionized water for quenching. The quenched material is taken out for secondary ball milling. The material after the secondary ball milling needs to be sieved through a 1000-mesh sieve and dried for standby use.
[0068] 3. LTCC bondable alloy paste
[0069] According to the ratio in Table 3, the organic carrier, inorganic binder phase and functional phase (including flaky gold powder and spherical gold powder) were weighed and placed in a tank, and premixed for 30 seconds at a low speed of 640r / min using a planetary gravity mixer, and then mixed for 60 seconds at a speed of 1260r / min and 120 seconds at a speed of 860r / min to obtain a fully mixed slurry. The mixed slurry was then rolled 8 to 10 times by a three-roll mill, wherein the roller spacing of the three-roll mill was adjusted between 5 and 100μm. After the particles inside the slurry were well dispersed, the fineness test (<20μm) and viscosity test (120~280Pa·s) were performed, and the finished slurry required for the experiment was obtained after filtration.
[0070] Performance measurement
[0071] (1) Take 30 pieces of FERRO A6 M-type LTCC green ceramic tapes with a thickness of 125 μm and a size of 5 inches and divide them into 3 groups, each with 10 pieces, numbered as experimental group 1, experimental group 2, and experimental group 3 respectively;
[0072] (2) Take one piece of green porcelain from each of Experimental Group 1, Experimental Group 2, and Experimental Group 3, respectively, and use a screen printer to print the bonding gold pastes in Examples 1-3 on the surfaces of the three pieces of green porcelain, respectively, and dry them at 60°C for 12 min;
[0073] (3) The film thickness of the printed gold paste in experimental group 1, experimental group 2, and experimental group 3 was measured using a laser measuring instrument, as shown in Table 4;
[0074] Table 4 Dry film thickness of gold paste printing at different positions
[0075]
[0076] The designed dry film thickness requirement is 12~18mm, and the three slurries meet the film thickness design requirements.
[0077] (4) Place each group of raw porcelain with gold paste printed on the top layer, and place the remaining 9 pieces of raw porcelain on the bottom layer to stack the raw porcelain layers;
[0078] (5) isostatically pressing the green porcelain tapes of Experimental Group 1, Experimental Group 2, and Experimental Group 3 to form green porcelain blanks. The isostatic pressing conditions are as follows: isostatic pressing pressure of 21 MPa, temperature of 70°C, and lamination time of 10 min.
[0079] (6) After debinding at 450°C and sintering at 850°C, the final LTCC substrate is obtained;
[0080] (7) The adhesion and bonding tensile force of the gold surface film layer of experimental group 1, experimental group 2, and experimental group 3 were tested. The experimental results are shown in Table 5.
[0081] The adhesion of electronic paste was evaluated by the stick-tear method. All three groups of experiments used the tape according to the adhesion test standard. No paste shedding was found after the test.
[0082] Gold wire bonding was performed on the surface of LTCC substrates in experimental group 1, experimental group 2, and experimental group 3 using ø25mm gold wire, and the bonding tension was tested. Referring to the requirements of GJB 548B-2005, the bonding tension of ø25mm gold wire should reach 3g. The test results are shown in Table 5. All three groups of experimental tests can meet the bonding tension requirements, and the bonding tension of experimental group 2 is relatively high.
[0083] Table 5 Bonding tensile test results
[0084]
[0085] Experimental conclusion:
[0086] In summary, by using 50% flaky gold powder, 30% spherical gold powder, 1% inorganic binder phase and 19% organic carrier, through strict control of the preparation process, gold surface paste that meets the design requirements can be produced.
Claims
1. A bondable alloy paste for LTCC co-firing, characterized in that: In terms of mass percentage, the bondable gold paste includes 75-85% of a micron-sized gold powder functional phase, 0.5-2% of an inorganic bonding phase and 18-20% of an organic carrier; the micron-sized gold powder includes flaky gold powder and spherical gold powder, and the mass ratio of the flaky gold powder to the spherical gold powder is 5:
3.
2. The bondable alloy paste for LTCC co-firing according to claim 1, characterized in that: The D50 of the flake gold powder in the micron-sized gold powder functional phase is 4±0.5 μm, and the D50 of the spherical gold powder is 2±0.5 μm.
3. The bondable alloy paste for LTCC co-firing according to claim 1, characterized in that: The inorganic binder phase is SiO2-B2O3-CaO glass powder, which includes 22.8% by weight of SiO2, 41.2% by weight of B2O3 and 36% by weight of CaO. The D50 of the SiO2-B2O3-CaO glass powder is 1±0.5 μm.
4. The bondable alloy paste for LTCC co-firing according to claim 1, characterized in that: The organic carrier comprises 65-85% by weight of an organic solvent, 10-30% by weight of a polymer thickener and 1-5% by weight of a thixotropic agent.
5. The bondable alloy paste for LTCC co-firing according to claim 4, characterized in that: The organic solvent is selected from any one or more of diethylene glycol monobutyl ether, diethylene glycol butyl ether acetate or alcohol ester dodecahydrate.
6. The bondable alloy paste for LTCC co-firing according to claim 4, characterized in that: The polymer thickener is ethyl cellulose.
7. The bondable alloy paste for LTCC co-firing according to claim 4, characterized in that: The thixotropic agent is selected from any one or more of hydrogenated castor oil and polyamide resin.
8. A method for preparing a bondable alloy paste for LTCC co-firing according to any one of claims 1 to 7, characterized in that: The following steps are involved: The micron-scale gold powder functional phase, inorganic bonding phase and organic carrier are uniformly stirred according to the ratio to obtain a fully mixed slurry; the slurry is rolled for multiple times until the slurry fineness and viscosity meet the requirements of screen printing, and then filtered to obtain a bondable gold surface slurry.
9. The preparation method according to claim 8, characterized in that: The preparation method of the inorganic binder phase comprises: Weigh CaO, B2O3 and SiO2 according to the ratio and put them into a ball mill. Use the ball mill to mix evenly and then dry the mixture. Then pour it into a platinum crucible and melt it at 1300-1500°C for 1-2 hours. Pour the molten glass liquid into deionized water for quenching. Take out the quenched material and perform secondary ball milling. After the secondary ball milling, filter the material with a 1000-mesh sieve and dry it for later use.
10. The preparation method according to claim 8, characterized in that: The stirring evenly comprises: In a ball mill, premix with a planetary gravity mixer at a low speed of 600-700 r / min for 30-60 s, then mix at a speed of 1200-1300 r / min for 60-90 s and at a speed of 800-900 r / min for 100-150 s to obtain a fully mixed slurry; The slurry is subjected to multiple rolling processes including: The mixed slurry is rolled on a three-roll mill for 8 to 10 times, wherein the roller spacing of the three-roll mill is adjusted between 5 and 100 μm; The slurry fineness that meets the requirements of screen printing is less than 20μm and the viscosity is 120~280Pa·s.